Preclinical Evaluation of Ga-DOTA-Minigastrin for the Detection of Cholecystokinin-2/Gastrin Receptor-Positive Tumors - Maarten Brom; Lieke Joosten; Peter Laverman; Wim J.G. Oyen; Martin Béhé; Martin Gotthardt; Otto C. Boerman (Molecular Imaging)
In comparison to somatostatin receptor scintigraphy, gastrin receptor scintigraphy using 111 In-DTPA-minigastrin (MG0) showed added value in diagnosing neuroendocrine tumors. We investigated whether the 68 Ga-labeled gastrin analogue DOTA-MG0 is suited for positron emission tomography (PET), which could improve image quality. Targeting of cholecystokinin-2 (CCK 2 )/gastrin receptor-positive tumor cells with DOTA-MG0 labeled with either 111 In or 68 Ga in vitro was investigated using the AR42J rat tumor cell line. Biodistribution was examined in BALB/c nude mice with a subcutaneous AR42J tumor. In vivo PET imaging was performed using a preclinical PET-computed tomographic scanner. DOTA-MG0 showed high receptor affinity in vitro. Biodistribution studies revealed high tumor uptake of 68 Ga-DOTA-MG0: 4.4 ± 1.3 %ID/g at 1 hour postinjection. Coadministration of an excess unlabeled peptide blocked the tumor uptake (0.7 ± 0.1 %ID/g), indicating CCK 2 /gastrin receptor-mediated uptake ( p = .0005). The biodistribution of 68 Ga-DOTA-MG0 was similar to that of 111 In-DOTA-MG0. Subcutaneous and intraperitoneal tumors were clearly visualized by small-animal PET imaging with 5 MBq 68 Ga-DOTA-MG0. 111 In- and 68 Ga-labeled DOTA-MG0 specifically accumulate in CCK 2 /gastrin receptor-positive AR42J tumors with similar biodistribution apart from the kidneys. AR42J tumors were clearly visualized by microPET. Therefore, 68 Ga-DOTA-MG0 is a promising tracer for PET imaging of CCK 2 /gastrin receptor-positive tumors in humans.